2018
DOI: 10.3389/fmed.2018.00262
|View full text |Cite
|
Sign up to set email alerts
|

Changing Antimicrobial Resistance Trends in Kathmandu, Nepal: A 23-Year Retrospective Analysis of Bacteraemia

Abstract: A comprehensive longitudinal understanding of the changing epidemiology of the agents causing bacteraemia and their AMR profiles in key locations is crucial for assessing the progression and magnitude of the global AMR crisis. We performed a retrospective analysis of routine microbiological data from April 1992 to December 2014, studying the time trends of non-Salmonella associated bacteraemia at a single Kathmandu healthcare facility. The distribution of aetiological agents, their antimicrobial susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(37 reference statements)
0
11
1
Order By: Relevance
“…The prevalence of MRSA in this study (68.5%) is higher than earlier studies of 12.5% and 8.0% from Gombe/North-eastern Nigeria (12,13). This could be attributable to variation in time/methodology and changes in prescribing habits of clinicians and pattern of resistance among the microorganisms as reported in other studies across the globe (15,16). However, differences (both higher and lower prevalence) with other Nigerian (9, 11) and foreign (5, 10, 17) studies have been observed in both MRSA and inducible clindamycin resistance.…”
Section: Discussioncontrasting
confidence: 65%
“…The prevalence of MRSA in this study (68.5%) is higher than earlier studies of 12.5% and 8.0% from Gombe/North-eastern Nigeria (12,13). This could be attributable to variation in time/methodology and changes in prescribing habits of clinicians and pattern of resistance among the microorganisms as reported in other studies across the globe (15,16). However, differences (both higher and lower prevalence) with other Nigerian (9, 11) and foreign (5, 10, 17) studies have been observed in both MRSA and inducible clindamycin resistance.…”
Section: Discussioncontrasting
confidence: 65%
“…However, individual antibiotic susceptibilities were not reported (125). In this study, the MDR non-Salmonella Enterobacterales, other Gram-negative organisms, and Gram-positive organisms accounted for 80%, 69%, and 70% of the isolates, respectively, in 2014.…”
Section: Nepalmentioning
confidence: 58%
“…Typhoid fever is frequently managed in the outpatient department (OPD) of the hospital and blood culture is routinely performed following routine microbiological procedures when enteric fever is suspected. 6 Antimicrobial susceptibility testing is performed by a modified Bauer-Kirby disc diffusion, with Etests Ò to determine MICs (bioMérieux, France); results are interpreted using CLSI guidelines. 7 In August and September 2019, routine microbiological diagnostic procedures identified three patients with Azith R S. Typhi attending the OPD.…”
Section: Main Textmentioning
confidence: 99%